Análisis de los protocolos de seguridad de la información en el Departamento de Catastros de Gad en la Cuidad de Jujan - Ronquillo Huacón, María Fernanda (2020)
Institutions or entities, regardless of their type, manage large amounts of data regarding their functions, giving way to the preparation of contingent protocols to protect different vulnerabilities. The objective of this investigation was aimed at analyzing information threats in the Department of Appraisals and Cadastre of the Municipal Autonomous Decentralized Government of the Canton Alfredo Baquerizo Moreno (Jujan) to adapt the systematic controls of computer security of ISO 27002 standard supported by the magerit methodology of the Ear / Pilar application (risk analysis and management system). Given the quantitative nature of our exploration, we opted for explanatory and descriptive research in each process of collecting foundations, and the survey technique directed at administrative personnel was also used. The result determined the importance of using a web server, expanding the collection windows, acquiring filing cabinets to protect the printed documents, obtaining an electric generator, the stability of the internet service and the protection of computer systems, both hardware and software. In conclusion, it has been possible to optimize the attention of the department in terms of its users, the risk index in the treatment and care of the information improved considerably.